Hofbauer cells of M2a, M2b and M2c polarization may regulate feto-placental angiogenesis. Issue 5 (November 2016) - Loegl, J; Hiden, U; Nussbaumer, E; Schliefsteiner, C; Cvitic, S; Lang, I; Wadsack, C; Huppertz, B; Desoye, G
Abstract : The human placenta comprises a special type of tissue macrophages, the Hofbauer cells (HBC), which exhibit M2 macrophage phenotype. Several subtypes of M2-polarized macrophages (M2a, M2b and M2c) exist in almost all tissues. Macrophage polarization depends on the way of macrophage activation and leads to the expression of specific cell surface markers and the acquisition of specific functions, including tissue remodeling and the promotion of angiogenesis. The placenta is a highly vascularized and rapidly growing organ, suggesting a role of HBC in feto-placental angiogenesis. We here aimed to characterize the specific polarization and phenotype of HBC and investigated the role of HBC in feto-placental angiogenesis. Therefore, HBC were isolated from third trimester placentas and their phenotype was determined by the presence of cell surface markers (FACS analysis) and secretion of cytokines (ELISA). HBC conditioned medium (CM) was analyzed for pro-angiogenic factors, and the effect of HBC CM on angiogenesis, proliferation and chemoattraction of isolated primary feto-placental endothelial cells (fpEC) was determined in vitro . Our results revealed that isolated HBC possess an M2 polarization, with M2a, M2b and M2c characteristics. HBC secreted the pro-angiogenic molecules VEGF and FGF2. Furthermore, HBC CM stimulated the in vitro angiogenesis of fpEC. However, compared with control medium, chemoattraction of fpEC toward HBC CM was reduced. Proliferation of fpEC was not affected by HBC CM. These findings demonstrate a paracrine regulation of feto-placental angiogenesis by HBC in vitro . Based on our collective results, we propose that the changes in HBC number or phenotype may affect feto-placental angiogenesis.